Estudo do desgaste por deslizamento de pares metálicos empregados no contato roda-trilho - Almeida, Leandro Prates Ferreira de (2017)
he study of wheel-rail contact is getting importantin Railway Engineering, especially because rail and wheel represent the second and third largest costs of materials on the railroad –the first is fuel. Usually, the end of life of these components is due to wear. The contact conditions changesaccording to the specificities of each railroad, such as load, speed, track design and materials used, among others. In order to understand the existing wear mechanisms for the typical contact conditions of the Estrada de Ferro Vitória a Minas, slip-wear tests were performed in the pin-on-disc configuration, without lubrication, with variable sliding speedand constant normal load. The spherical end pinswere manufactured from conventional EFVM rail material -370 Brinell surface hardness pearlitic steel -and the discs were manufacturedfrom AAR grade Class C cast and forged wheel material. The worn volume of the pins was calculated based on the diameter of the wear scar. Forthe discs, the worn volume was obtained by 3D profilometry. The wear mechanisms were analyzed using a stereoscopic microscope and a scanning electron microscope. The results indicate an increase in the coefficient of friction in the tests at a speedof 0.9 m/s -μapproximately 0.8 -when compared to the values obtained at a speedof 0.1 m/s -μbetween 0.5 and 0.6. The wear severity of both pins and discs was higher in the tests carried out with a sliding speed of 0.1 m/s. Comparing the different materials of the discs, the wear of pins and discs was considerably greater in systems with forged wheels. The wear mechanisms observed were predominantly of plastic nature, with occurrence of ploughingand adhesion of oxidized materials on the surface of pins and discs